SEGURIDAD NACIONAL SOCIAL CONFLICTS IN THE PUNO REGION AND ITS EFFECTS ON NATIONAL SECURITY - Ancco , Rodrigo (2023)
One of the problems that afflicts the country in recent times are social conflicts, which are generated by multiple factors and that influence the behavior of a population group, such as unsatisfied demands that have not been resolved by the State and which leads to social protests; In this sense, this work aimed to “Analyze the management of the state in the social conflicts of the Puno region and its effect on National Security” within the framework of the events after December 7, 2022, after the coup attempt. of the state by former president Pedro Castillo Terrones. As a method, a qualitative approach, descriptive and hermeneutical, was used, reviewing bibliography, journalistic data and interviews. As a result, it was determined that the management of social conflicts by the State has not been entirely satisfactory. It was concluded that the social conflicts in Puno were not due to social demands, but rather to policies influenced by left-wing ideologies and national and foreign political groups.